Impact of extra-corporeal membrane oxygenation on outcome of aluminium phosphide poisoning complicated with myocardial dysfunction. (2nd November 2019) - Mohan, Bishav; Gupta, Vivek; Ralhan, Sarju; Gupta, Dinesh; Puri, Sandeep; Mahajan, Rajesh; Goyal, Abhishek; Chhabra, Shibba; Tandon, Rohit; Aslam, Naved; Wander, Gurpreet Singh; Singh, Bhupinder
Abstract: Background: Aluminium phosphide (AlP) poisoning is associated with a high mortality rate when patients are complicated with myocardial dysfunction and refractory shock or severe metabolic acidosis. We studied the role of veno-arterial extra-corporeal membrane oxygenation (VA-ECMO) in patients of AlP poisoning induced myocardial dysfunction. Methods and results: This is a tertiary care, single-centre, retrospective study. Between January 2011 and June 2016, total of 107 patients with AlP poisoning were identified and of those 67 were categorised in high-risk category as per the criteria. The in-hospital mortality of patients who received ECMO ( n = 35) was compared to those who received conventional treatment ( n = 32) only. The use of ECMO in addition to conventional treatment has reduced the in-hospital mortality from 84.4% to 40% (odds ratio: 0.47; 95% confidence interval 0.31–0.73). Among survivors, the ECMO group had a significantly lower baseline left ventricular ejection fraction (LVEF; median: 24%; IQR: 22–29 vs. median: 32%; IQR: 32–33.5; p < .003) but a non-significantly higher LVEF at the time of discharge (median: 52%; IQR: 48–60 vs. median: 48%; IQR: 47–49; p : .064) than did the conventional group. On logistic regression analysis the higher sequential organ failure assessment (SOFA) score, lower pH and the non-usage of ECMO were found to be the independent predictors of mortality. Conclusion: The use of ECMO in high-risk patient of AlP poisoning has resulted in a significant reduction in the mortality. A high baseline SOFA score has been found to be the independent predictor of mortality.